Region-specific neuroprotective effects of meldonium pretreatment in two models of sepsis-associated encephalopathy - Ružičić, Aleksandra; Srdić, Tijana; Bobić, Katarina; Drakulić, Dunja; Veljković, Filip; Todorović, Ana; Đurašević, Siniša; Lakić, Iva (Frontiers in Pharmacology, 2025)
Sepsis-associated encephalopathy (SAE) is a common yet poorly understood complication of sepsis, which poses a burden in clinical settings, as its management relies on supportive care without targeted pharmacological interventions. Meldonium is a drug approved for ischemic heart disease but has also gained attention for its neuroprotective effects. In animal models of sepsis, meldonium pretreatment exerted antioxidative, antiapoptotic, and anti-inflammatory effects, but its neurological effects have not been studied in SAE. In the present study, rats were pretreated with meldonium for 4 weeks, before sepsis was induced via a faecal intraperitoneal injection (FIP) or a lipopolysaccharide (LPS) injection. The cerebellum, medulla oblongata, and prefrontal cortex were examined due to their involvement in functions that are often impaired in sepsis. Eight hours post-sepsis induction, markers of brain injury were assessed, including reflexes scores, dry to wet brain mass ratio, prooxidant-antioxidant balance (PAB), advanced oxidation protein products (AOPP), lipid peroxidation (LPO), phosphatidylcholine (PC) to lysophosphatidylcholine (LPC) ratio, HMGB1 and haptoglobin protein expression, and CD73 activity. Meldonium-pretreated FIP-septic rats showed an earlier decline in reflex scores compared to the sepsis-only group, accompanied by a slight brain water accumulation. However, in both models of sepsis, meldonium pretreatment prevented alterations in the PAB, AOPP, and LPO in a region-specific manner. It also preserved the PC/LPC ratio in the prefrontal cortex of FIP-septic rats and in all regions of LPS-septic rats. Haptoglobin protein content was altered only in FIP-septic rats, and preserved by meldonium pretreatment in the cerebellum and medulla oblongata of these rats. Additionally, meldonium pretreatment preserved CD73 activity in the medulla oblongata and prefrontal cortex of FIP-septic rats and in the cerebellum and prefrontal cortex of LPS-septic rats. In conclusion, our study is the first to demonstrate that pretreatment with meldonium, a drug that has shown neuroprotective effects in other invasive models can also provide benefits in SAE, with the extent of protection depending on both the model of sepsis induction and the specific brain region investigated. Our findings support the discussion on the importance of selecting the right sepsis model and studying individual brain regions when investigating SAE and potential therapeutic approaches.